Analisis Kesalahan Penalaran Matematis Dalam Menyelesaikan Masalah Pola Bilangan Ditinjau Dari Gaya Belajar - Ismul Hadi; Sri Subarinah; Tabita Wahyu Triutami; Nurul Hikmah (Griya Journal of Mathematics Education and Application, 2022)
This study aims to describe the types of reasoning errors made in solving number pattern problems. Based on mathematical reasoning procedures, error analysis was carried out based on student learning styles. The stages of mathematical reasoning in this study include the stages proposing conjectures, finding patterns, and drawing conclusions. The research subjects for class VIII A of SMPN 8 Mataram for the academic year 2021/2022 were selected by purposive sampling. To deepen the research results, two students were selected from each type of learning style. The instruments in this study are learning style questionnaires, number pattern tests, and interview guidelines. The data analysis technique used quantitative and qualitative data analysis techniques. From the results of the study, we obtained the percentage of mathematical reasoning errors, namely: (i) students with visual learning styles at the stage of proposing a guess made 42%, finding patterns 72%, and drawing conclusions 71%; (ii) students with auditory learning styles stage proposed 53% conjectures, finding patterns 67%, and drawing conclusions 70%; (iii) students with a kinesthetic learning style stage proposed 56% conjectures, finding patterns 67%, and drawing conclusions 70%; (iv) the causes of student errors with visual, auditory, and kinesthetic learning styles are a lack of understanding of number pattern material, a lack of thoroughness in calculations, a lack of thoroughness in understanding questions, and a lack of experience with concluding final results.